PENGEMBANGAN MODEL MISSOURI MATHEMATICS PROJECT (MMP) BERBASIS BUDAYA MELAYU DENGAN BERBANTUAN GAME EDUKATIF WORDWALL UNTUK MENINGKATKAN NUMERASI SISWA SMP SWASTA Al WASHLIYAH 8 MEDAN - Nasution, Aurora Pradizka; Yumira Simamora; Jihan Hidayah Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a Missouri Mathematics Project (MMP) learning model based on Malay culture with the assistance of the educational game Wordwall to improve junior high school students’ numeracy skills. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 40 eighth-grade students of SMP Swasta Al Washliyah 8 Medan. The results showed that the developed MMP model based on Malay culture was valid, practical, and effective in enhancing students’ numeracy abilities. The model’s validity, obtained through validation by material experts, media experts, and cultural experts, reached an average of 96.6% (very valid category). The practicality of the model, assessed by teachers and students, achieved an average score of 88.6% (very practical category). The learning effectiveness was reflected in the improvement of students’ numeracy test results, with an N-Gain score of 0.86 (high category). The integration of Malay culture in mathematics learning provided a more meaningful context for students, while the use of Wordwall increased engagement and learning motivation. Therefore, this model is feasible to be implemented as an innovative learning alternative to improve students’ literacy and numeracy skills at the junior high school level.